Developing an exercise intervention to minimise hip bone mineral density loss following traumatic lower limb amputation : a Delphi study - Behan, Fearghal P.; Bull, Anthony M.J.; Beck, Belinda R.; Brooke-Wavell, Katherine; Müller, Ralph; Vico, Laurence; Isaksson, Hanna ; 0000-0002-9690-8907; Harvey, Nicholas C.; Buis, Arjan; Sherman, Kate; Jefferson, Gemma; Cleather, Daniel J.; et al. (British Journal of Sports Medicine, 2024)
Objective To elicit expert opinion and gain consensus on specific exercise intervention parameters to minimise hip bone mineral density (BMD) loss following traumatic lower limb amputation. Methods In three Delphi rounds, statements were presented to a panel of 13 experts from six countries. Experts were identified through publications or clinical expertise. Round 1 involved participants rating their agreement with 22 exercise prescription statements regarding BMD loss post amputation using a 5-point Likert scale. Agreement was deemed as 3–4 on the scale (agree/strongly agree). Statements of <50% agreement were excluded. Round 2 repeated remaining statements alongside round 1 feedback. Round 3 allowed reflection on round 2 responses considering group findings and the chance to change or maintain the resp onse. Round 3 statements reaching ≥70% agreement were defined as consensus. Results All 13 experts completed rounds 1, 2 and 3 (100% completion). Round 1 excluded 12 statements and added 1 statement (11 statements for rounds 2–3). Round 3 reached consensus on nine statements to guide future exercise interventions. Experts agreed that exercise interventions should be performed at least 2 days per week for a minimum of 6 months, including at least three different resistance exercises at an intensity of 8–12 repetitions. Interventions should include weight-bearing and multiplanar exercises, involve high-impact activities and be supervised initially. Conclusion This expert Delphi process achieved consensus on nine items related to exercise prescription to minimise hip BMD loss following traumatic lower limb amputation. These recommendations should be tested in future interventional trials.